Neuroplastin-55 is a receptor of Manf and protects against diet-induced obesity by promoting adipose browning - Qingyi Jia; Jinhang Zhang; Haiying Song; Jiahao Chen; Zhenyu Zhang; Huihui Yu; Yi Chen; Qinhui Liu; Xiandan Jing; Haixia Xu; Jingwei Li; Yimin Xiong; et al. (Proceedings of the National Academy of Sciences, 2025)
The browning of white adipose tissue (WAT) enhances thermogenesis and holds great potential in obesity treatment. Membrane receptors have been proven as essential factors during WAT browning. In this study, we found that transmembrane receptor neuroplastin-55 (Np55) was markedly upregulated in the adipose tissue of both obese individuals and mice. Fat-specific Np55 knockout (Np55 FKO ) sensitized mice to high-fat diet-induced obesity and metabolic disorders, which was attributed to impaired energy expenditure and WAT browning. We identified that mesencephalic astrocyte-derived neurotrophic factor (Manf) acts as a ligand for Np55 with high binding affinity. Mechanistically, Np55 forms a complex with tumor necrosis factor receptor associated factor-2 (TRAF2) and apoptosis signal-regulating kinase 1 (ASK1) to activate p38 mitogen-activated protein kinase (MAPK) signaling pathway and conduct WAT browning after Manf stimulation. Additionally, we identified a single-nucleotide polymorphism (rs2470738600) in Manf compromised the binding affinity to Np55 and thermogenic capacity. Finally, we showed that Np55 is indispensable for Manf-induced thermogenesis and weight loss in obese mice. Our results underscore the pivotal role of Np55 as a receptor of Manf in maintaining metabolic homeostasis, highlighting its potential as a therapeutic target for obesity and related disorders.